PERGESERAN DARI GERAKAN BERBASIS KULTURALISME KE GERAKAN PURITANISME - Maltifal Maltifal; Agusrianto Agusrianto; Mursal Mursal; Ahmad Lahmi (Ensiklopedia of Journal, 2026)
The culturalist and puritanical movements are two important currents in the dynamics of Islamic religious thought and practice. Culturalism emphasizes a dialogical approach between religious teachings and local socio-cultural realities, while puritanism focuses on purifying religious teachings based on normative sources deemed authentic. The shift from culturalism to puritanism is a complex phenomenon that cannot be understood through a single discipline alone. Therefore, this paper aims to analyze the basic concepts, historical background, characteristics, and socio-religious implications of this shift through a multidisciplinary approach, encompassing theological, sociological, anthropological, historical, political, and philosophical perspectives. This research employs qualitative methods with a literature review approach and descriptive-critical analysis. The results indicate that the shift from culturalism to puritanism is influenced by changes in religious understanding, social transformation, globalization, and the dynamics of authority and power within Muslim societies. This study emphasizes the importance of an integrative and contextual approach so that the dynamics of religiosity can develop moderately and constructively, avoiding tendencies toward extremism and cultural relativism.  Keywords: culturalism; puritanism; religious movements; Islam; multidisciplinary approach; contemporary Islam